Removal of H3K27me3 by JMJ Proteins Controls Plant Development and Environmental Responses in Arabidopsis - Yamaguchi, Nobutoshi (Frontiers in Plant Science, 2021)
Trimethylation of histone H3 lysine 27 (H3K27me3) is a highly conserved repressive histone modification that signifies transcriptional repression in plants and animals. In Arabidopsis thaliana, the demethylation of H3K27 is regulated by a group of JUMONJI DOMAIN-CONTANING PROTEIN (JMJ) genes. Transcription of JMJ genes is spatiotemporally regulated during plant development and in response to the environment. Once JMJ genes are transcribed, recruitment of JMJs to target genes, followed by demethylation of H3K27, is critically important for the precise control of gene expression. JMJs function synergistically and antagonistically with transcription factors and/or other epigenetic regulators on chromatin. This review summarizes the latest advances in our understanding of Arabidopsis H3K27me3 demethylases that provide robust and flexible epigenetic regulation of gene expression to direct appropriate development and environmental responses in plants.